STUDY OF THE EFFECT OF PRECURSORS ON THE STRUCTURAL CHARACTERISTICS OF SYNTHETIZED ZNO NANOPARTICLES - ASAULYUK, TATYANA; SARIBYEKOVA, YULIA; SEMESHKO, OLGA; KULISH, IRINA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In this work, zinc oxide (ZnO) nanoparticles were obtained by direct precipitation method in aqueous solution using two different precursors — zinc acetate dihydrate and zinc chloride — under the same synthesis conditions. The effect of the selected precursors on the structural parameters of each synthesized sample was evaluated using X-ray diffraction (XRD) analysis. The results of the analysis demonstrate the synthesized ZnO phase with a hexagonal wurtzite structure and the average crystallite size of 28 nm for both studied samples. Based on the XRD data, the interplanar spacing, crystallite size, dislocation density, and micro strain were determined for different crystallographic planes. Analysis of the obtained values shows slight differences in the formed crystalline materials depending on the used precursor. The calculated structural parameters of the synthesized ZnO nanoparticles are in good agreement with the standard reported data (JCPDS 36-1451). The effect of selected precursors on the lattice constants, unit cell volume, Zn–O bond length, and crystallinity of synthesized ZnO samples was studied. It was established that the sample obtained from the zinc acetate dihydrate precursor is characterized by the absence of impurities and higher crystallinity (93%) compared to the sample synthesized from zinc chloride, the crystallinity of which is 86%. The results are of practical value for simple synthesis of nano dispersed forms of ZnO and its possible application in textile finishing.